Letter from Siberia - Marker, Chris (France, 1957)
This personal essay uses the form of a letter from Siberia as its launch pad, before moving off in various different directions: the documentary becomes a travelogue, an animated cartoon, and then a philosophical tract, continuously changing genres. Marker's left-wing intellectual views foreground his filming and commentary, but the director's voiceover remains playful and reflexive. Letter from Siberia was banned from Karlovy Vary Film Festival in Czechoslovakia on the request of Soviet officials.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films